The master puppeteer - Paterson, Katherine (New York : HarperTrophy, 1989)
A thirteen-year-old boy describes the poverty and discontent of eighteenth century Osaka and the world of puppeteers in which he lives.
5.8
5-8
7-9
Keywords: Puppets -- Juvenile fiction; Puppets -- Fiction; Puppets and puppet plays -- Fiction; Japan -- Juvenile fiction; Japan -- Fiction; Japan -- Fiction